Involvement of the population of the region in online participation: experience of non-profit organisations - K. E. Kosygina (Вестник университета)
The study examines the practices and problems of online involvement of the population in the activities of non-profit sector organisations depending on socio-demographic characteristics based in statistical observation, and data from a sociological survey on the territory of the Vologda region. It has been substantiated that when implementing socially significant projects and events, it is advisable for non-profit organisations to assess the territorial features of digitalisation, the possibilities of potential and target audiences. A toolkit for assessing the involvement of the population in the activities of non-profit organisations in the digital environment has been proposed based on the analysis of three parameters: awareness, goal-setting, and the effectiveness of online platforms and its approbation has been carried out. A portrait of a user of the network resources of non-profit organisations has been presented. It has been concluded that at present society is more focused on the implementation of the practices of civic participation in real, and not in the virtual space, which is shown by the experience of non-profit organisations.